2007
DOI: 10.1101/lm.749207
|View full text |Cite
|
Sign up to set email alerts
|

Perirhinal cortex resolves feature ambiguity in configural object recognition and perceptual oddity tasks

Abstract: The perirhinal cortex (PRh) has a well-established role in object recognition memory. More recent studies suggest that PRh is also important for two-choice visual discrimination tasks. Specifically, it has been suggested that PRh contains conjunctive representations that help resolve feature ambiguity, which occurs when a task cannot easily be solved on the basis of features alone. However, no study has examined whether the ability of PRh to resolve configural feature ambiguity is related to its role in object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
149
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(162 citation statements)
references
References 40 publications
12
149
0
1
Order By: Relevance
“…Interestingly, the performance of MTL-damaged patients deviated from control performance in two ways: first, they reported seeing the Familiar Configurations as figure somewhat less often than controls, and second, they reported seeing the Part-Rearranged Novel Configurations as figure more often than controls. Taken alone, the first finding is consistent with the theoretical view that the PRC of the MTL contains representations of complex configurations Lee et al, 2005;Barense et al, 2005Barense et al, , 2007Barense et al, , 2010a; Bartko et al, 2007;Lee and Rudebeck, 2010;Burke et al, 2011), and damage to these configural representations removes effects of configuration familiarity on figure assignment. Taken together, however, the two findings suggest that either output from the PRC is privileged over that from lower-level visual regions during figure-ground assignment (a feedforward explanation for the data) or that the intact PRC plays a role in modulating processing in lower-level visual areas (a feedback explanation).…”
Section: Introductionsupporting
confidence: 77%
“…Interestingly, the performance of MTL-damaged patients deviated from control performance in two ways: first, they reported seeing the Familiar Configurations as figure somewhat less often than controls, and second, they reported seeing the Part-Rearranged Novel Configurations as figure more often than controls. Taken alone, the first finding is consistent with the theoretical view that the PRC of the MTL contains representations of complex configurations Lee et al, 2005;Barense et al, 2005Barense et al, , 2007Barense et al, , 2010a; Bartko et al, 2007;Lee and Rudebeck, 2010;Burke et al, 2011), and damage to these configural representations removes effects of configuration familiarity on figure assignment. Taken together, however, the two findings suggest that either output from the PRC is privileged over that from lower-level visual regions during figure-ground assignment (a feedforward explanation for the data) or that the intact PRC plays a role in modulating processing in lower-level visual areas (a feedback explanation).…”
Section: Introductionsupporting
confidence: 77%
“…Lesion studies involving rats and monkeys indicate that lesions of the perirhinal cortex typically disrupt object recognition; however, hippocampal lesions produce variable results on object recognition tasks (Murray et al 2000). Specifically, studies have shown that the perirhinal cortex may distinguish between visual objects with overlapping features to reduce feature ambiguity (Bussey et al 2003Gilbert and Kesner 2003;Norman and Eacott 2004;Bartko et al 2007). However, there is some evidence to suggest that the hippocampus may play little role in disambiguating object features .…”
mentioning
confidence: 99%
“…Lesion studies involving rats and monkeys indicate that lesions of the perirhinal cortex typically disrupt object recognition; however, hippocampal lesions produce variable results on object recognition tasks (for review, see Murray et al 2000). Specifically, studies have shown that the perirhinal cortex may function to distinguish between visual objects with overlapping features to reduce feature ambiguity (Bussey et al 2002Gilbert and Kesner 2003;Norman and Eacott 2004;Bartko et al 2007). However, some studies have suggested that the hippocampus may play little role is disambiguating object features .…”
mentioning
confidence: 99%